Operational excellence through passive RFID: Rapid deployment solutions for indoor localization - Chang, Mike C.; Martinez, Stanford; Alaeddini, Adel; Wan, Hung-da (BOHR International Journal of Operations Management Research and Practices, 2025)
The demand for indoor positioning has grown significantly due to applications that rely on location awareness in spaces such as medical facilities, warehouses, and smart buildings. Unlike outdoor environments, where global positioning system operates effectively, indoor positioning faces the challenges of signal blocking and multipath effects common in enclosed areas. Current solutions such as Wi-Fi, Bluetooth, and Ultra-Wideband (UWB) provide effective results, but they often involve high costs and complex install processes, especially in big settings. Given these challenges, passive radio frequency identification (RFID) has become a viable choice for indoor positioning. Not only the technology is cost-effective, but also eliminates the need of active power supply to its tags, making efficiency increase. This paper is proposing a passive RFID-based positioning system which designed for rapid deployment to solve signal interference, a common problem in the area with neighboring small spaces. We explore the limitations of the current RFID system and propose simple strategies to ensure location accuracy with minimal installation needs.